Projection algorithms for calculating the Roben potential - Lezhnev, V.G.; Markovsky, A.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2019)
Several projection algorithms of the basic potential method are proposed for calculating the density of the Roben potential. The completeness of a special system of potentials is proved.